O baculejo: a abordagem policial na periferia de Fortaleza - Silva, Thiago do Nascimento (2021)
The approach performed by security agents on individuals can occur in different situations and locations. When entering a stadium to watch a soccer game, during a traffic stop, in planned police operations, while using public transport, etc. The present work represents the attempt to build an ethnography on those aimed at certain parts of the population, specifically the blacks, the poor and residents of the periphery. Violent approaches to their bodies are called baculejo in Fortaleza and other cities. In these moments, police action is marked by the use of extra-legal procedures, with illegitimate violence being a constant. With direct observation and contact with interlocutors in the field, I present a reading of the phenomenon based on the meanings attributed by the subordinate part of the relationship. I seek to delve into the practices that constitute the phenomenon, reflecting on the positions of the agents involved and the power relations and world demarcations that are established. I discuss topics that involve police activity, such as discretion, well-founded suspicion and the use of legitimate violence. During their work, police agents make use of both the formal codes established by the State and the set of moral economies present in their institutions and in themselves.